Morphological comparison of artificial teeth position utilising denture space in glossectomy patients. (9th December 2019) - Awuti, Shataer; Sumita, Yuka I.; Hattori, Mariko; Yoshi, Shigen; Kelimu, Shajidan; Ohbayashi, Naoto; Kurabayashi, Tohru; Taniguchi, Hisashi
Abstract: Objective: This study aimed to compare the denture space of edentulous glossectomy patients with that of a control group from the perspective of artificial teeth positioning by using three‐dimensional techniques. Background: It is known that the shape of the denture space may be affected by tongue resection or reconstruction. However, the details of artificial teeth positioning in these patients remain unclear. Materials and methods: Six edentulous glossectomy patients aged 73‐83 years and six normal participants aged 74‐85 years participated in the study. Piezography was used to elucidate the characteristics of the denture space. For visualisation, piezographic records were scanned using cone beam computed tomography and the data were converted into stereolithographic format. Three‐dimensional images of piezographic records were then constructed. Bucco‐lingual widths of the mandibular occlusal surface were reproduced, and the camber line of the occlusal surface was set so as to simulate the position of the artificial teeth. The maximum chord of the occlusal surface on the left and right sides was recorded and measured. The discrepancy and ratio of the larger chord to the smaller chord between the right and left sides was calculated and subjected to statistical analyses using the Mann‐Whitney U test. Results: There were significant differences in discrepancy and ratio between the left and right in the control group and the glossectomy patients ( P  ˂ .01). The glossectomy patients showed a greater discrepancy and ratio than the control group. Conclusions: The simulated artificial teeth positions on the occlusal surface between the right and left side were asymmetric in glossectomy patients.